The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1037/0021-9010.86.6.1232
|View full text |Cite
|
Sign up to set email alerts
|

Bothered by abstraction: The effect of expertise on knowledge transfer and subsequent novice performance.

Abstract: Although experts should be well positioned to convey their superior knowledge and skill to novices, the organization of that knowledge, and particularly its level of abstraction, may make it difficult for them to do so. Using an electronic circuit-wiring task, the authors found that experts as compared with beginners used more abstract and advanced statements and fewer concrete statements when providing task instructions to novices. In a 2nd study, the authors found that beginner-instructed novices performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
190
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(204 citation statements)
references
References 33 publications
8
190
2
4
Order By: Relevance
“…As a result, there is little evidence to suggest at what point this form of gaze following ceases to be useful, or whether similar performance gains could arise from following a novice's eye movements. It is encouraging that more studies are examining collaborative visual search, yet the assertion that expert eye movements should be especially useful in training novices where to look neglects the possibility that a peer's eye movements could also be useful in directing attention (see Brennan et al, 2008;Stein & Brennan, 2004; see also Hinds, Patterson, & Pfeffer, 2001). That is, even the extensive literature on gaze perception has yet to determine if we follow another's gaze based on whether the person is an "expert" or "novice."…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is little evidence to suggest at what point this form of gaze following ceases to be useful, or whether similar performance gains could arise from following a novice's eye movements. It is encouraging that more studies are examining collaborative visual search, yet the assertion that expert eye movements should be especially useful in training novices where to look neglects the possibility that a peer's eye movements could also be useful in directing attention (see Brennan et al, 2008;Stein & Brennan, 2004; see also Hinds, Patterson, & Pfeffer, 2001). That is, even the extensive literature on gaze perception has yet to determine if we follow another's gaze based on whether the person is an "expert" or "novice."…”
Section: Discussionmentioning
confidence: 99%
“…This not only means that they perform very fast and tend to skip steps (Blessing and Anderson 1996;Kalyuga and Sweller 2004), which might make it difficult for students to see or follow what the model is doing but also means that the model may have difficulty verbalizing what s/he is doing because the performance does not require controlled processing (Feldon 2007). It has also been suggested that the level of abstraction of instructions provided by experts may pose problems for novices' understanding and that instructions provided by somewhat advanced individuals led to better task performance (Hinds et al 2001). On the other hand, the higher level of abstraction in expert instructions seemed to be more beneficial for solving novel tasks (i.e., transfer; Hinds et al 2001).…”
Section: How Should Examples Be Designed To Optimize Their Effectivenmentioning
confidence: 99%
“…It has also been suggested that the level of abstraction of instructions provided by experts may pose problems for novices' understanding and that instructions provided by somewhat advanced individuals led to better task performance (Hinds et al 2001). On the other hand, the higher level of abstraction in expert instructions seemed to be more beneficial for solving novel tasks (i.e., transfer; Hinds et al 2001). Moreover, expert models might be more effective for advanced students to learn from, as they might be less bothered by the skipping of steps, as their own knowledge base is closer to that of the expert and they are more likely to know what the relevant aspects of performance are that they need to attend to (cf.…”
Section: How Should Examples Be Designed To Optimize Their Effectivenmentioning
confidence: 99%
“…First, automated knowledge may be omitted from procedural explanations (e.g., Cooke & McDonald, 1987;de Groot & Gobet, 1996;Gruber, 1989;Hinds, Patterson, & Pfeffer, 2001). Second, novices process task-relevant information in a fundamentally different way than do experts.…”
Section: Discussionmentioning
confidence: 99%